Complete mitochondrial genome of the Korean endemic springtail Homidia koreana Lee & Lee, 1981 (Collembola: Entomobryidae). Issue 1 (2nd January 2022) - Lee, Inae; Koo, Jachoon; Park, Kyung-Hwa
Abstract: The Korean endemic springtail Homidia koreana Lee & Lee, 1981 is popular in the leaf litter of various forests of South Korea, probably widely distributed throughout the Korean Peninsula. The complete mitochondrial genome of H. koreana was sequenced, assembled, and annotated. The mitochondrial genome of H. koreana consists of a circular DNA molecule of 14, 846  bp, with 68.4% AT content. It comprises 13 protein-coding genes (PCGs), 22 transfer (tRNA) genes, and 2 ribosomal RNA (rRNA) genes. The molecular phylogenetic relationships estimated using MrBayes 3.2 revealed that H. koreana was closely related to Homidia socia Denis, 1929, both of which belong to the genus Homidia .